Phoenix sylvestris, Wild Date Palm - Robert J. Northrop; Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS)
FOR 246, a 2-page fact sheet by Robert J. Northrop, Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this slow-growing palm native to India and southern portions of Pakistan – scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.